PVHL‐mediated degradation of HIF‐2α regulates estrogen receptor α expression in normoxic breast cancer cells. Issue 16 (4th July 2016) - Higashimura, Yasuki; Kitakaze, Tomoya; Harada, Naoki; Inui, Hiroshi; Nakano, Yoshihisa; Yamaji, Ryoichi
Abstract : Estrogen receptor α (ERα) functions as a transcription factor for genes involved in estrogen‐dependent development of breast cancer cells. We demonstrate here that knockdown of hypoxia‐inducible factor (HIF)‐2α, but not of HIF‐1α, increases endogenous ERα protein expression in normoxia and hypoxia. The von Hippel–Lindau protein (pVHL)‐dependent degradation of HIF‐2α participates in the regulation of ERα expression. Additionally, HIF‐2α forms a protein complex with ERα, and amino acids 396–823 of HIF‐2α physically interact with the ligand‐binding domain of ERα. These results indicate that HIF‐2α functions as a negative regulator of ERα expression in breast cancer, especially in normoxia. Abstract :